(untitled) (ModaPalavra e-periódico, 2015)
Guided by bibliographical and field research, and case studies, this paper presents a reflection around a production process model in fashion design area focused on sustainability. It is a methodology that includes the redesign of thrift store clothes, discarded and devalued because they are out of fashion trends, which may undergo a upcycling process, extending its life cycle and turning to have aesthetic value and Marketplace. The objective is even in a small part, contribute to the environment in a creative and innovative way, with the difference the fact of enabling the reproduction of parts in scale without losing the exclusivity.